2021
DOI: 10.1017/s0007114521001410
|View full text |Cite
|
Sign up to set email alerts
|

Food sources of iodine in schoolchildren and relationship with 24-h urinary iodine excretion in Victoria, Australia

Abstract: Dietary recalls have been used previously to identify food sources of iodine in Australian schoolchildren. Dietary assessment can provide information on the relative contributions of individual food groups which can be related to a robust objective measure of daily intake (24hr urinary iodine excretion (UIE)). In Australia, the government has mandated the use of iodised salt in breadmaking to address iodine deficiency. The aim of this study was to determine the dietary intake and food sources of iodine to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Taking the average bread consumption, the aimed value for salt in its production, and the average iodine content in salt found in this study, bread alone can represent a daily iodine intake of nearly 18 µg (12.2% of the daily requirement). Strategies of using iodized salt in bread production have been successfully applied to increase iodine intake adequacy elsewhere [ 47 , 48 ]. The contribution to the daily iodine intake of fruits, vegetables, and legumes observed in this study is in line with the previously reported iodine content of Portuguese foods [ 18 ] and already demonstrated in the literature [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking the average bread consumption, the aimed value for salt in its production, and the average iodine content in salt found in this study, bread alone can represent a daily iodine intake of nearly 18 µg (12.2% of the daily requirement). Strategies of using iodized salt in bread production have been successfully applied to increase iodine intake adequacy elsewhere [ 47 , 48 ]. The contribution to the daily iodine intake of fruits, vegetables, and legumes observed in this study is in line with the previously reported iodine content of Portuguese foods [ 18 ] and already demonstrated in the literature [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary Iodine Excretion (UIE) is an indicator of iodine status, because most of the iodine absorbed by the body will be excreted in the urine and can reflect current iodine intake and recent changes in a person's iodine status (Campanozzi et al, 2019). Examination of UIE a sensitive marker to determine a long-term effect of iodine intake for months to years (Beckford et al, 2022). Adequate intake of iodine can increase complete brain development at the age of 7 years until 15 (Murcia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%